ANALISIS PENGENDALIAN INTERN SIKLUS PENJUALAN PADA UD. SEHAT INDAH DI GORONTALO - Maria, Brigita; Nangoi, Grace B; Mintalangi, Syermi S.E (Universitas Sam Ratulangi, 2020)
A sales cycle that is reached out well in a company due to the role of an adequate intern control. The applied of intern control can be used as supervision and can increase effectiveness in sales activities in the company. The purpose of this study was to determine how the applied and implementation of intern Â control of the sales cycle at UD. Sehat Indah Gorontalo. This type of research is descriptive qualitative. The analytical method used in this research is a descriptive method, where the research results are described in accordance with the actual situation obtained directly through interviews and documentation. Research result obtained indicate that intern control in the sales cycle at UD. Sehat Indah has been quite effective, however the implementation is not yet fully adequate, because there are still weaknesses and incompatibilities with one of the concepts of internal control.